Bored and brilliant : how spacing out can unlock your most productive and creative self - Zomorodi, Manoush (St. Martins Press, 2017)
"Explains the connection between boredom and original thinking, exploring how we can harness boredom's hidden benefits to become our most productive and creative selves without totally abandoning our gadgets in the process. Grounding the book in the neuroscience and cognitive psychology of 'mind wandering' - what our brains do when we're doing nothing at all - Manoush includes practical steps you can take to ease the nonstop busyness and enhance your ability to dream wonder, and gain clarity in your work and life."--Dust jacket flap.